Coronary microvascular dysfunction and myocardial contractile reserve in women with angina and no obstructive coronary artery disease. Issue 2 (8th December 2017) - Michelsen, Marie M.; Pena, Adam; Mygind, Naja D.; Bech, Jan; Gustafsson, Ida; Kastrup, Jens; Hansen, Henrik S.; Høst, Nis; Hansen, Peter R.; Prescott, Eva
Abstract : Background: Coronary microvascular dysfunction (CMD) is a potential cause of myocardial ischemia and may affect myocardial function at rest and during stress. We investigated whether CMD was associated with left ventricular diastolic and systolic function at rest and during pharmacologically induced hyperemic stress. Methods: In a prospective cohort study, we included 963 women with angina, left ventricular ejection fraction (LVEF) >45%, and an invasive coronary angiogram without significant stenosis (<50%). Parameters of left ventricular diastolic function, LVEF, speckle tracking–derived global longitudinal strain (GLS), and coronary flow velocity reserve (CFVR) were assessed by transthoracic echocardiography at rest and during dipyridamole stress. The GLS and LVEF reserves were defined as the absolute increases in GLS and LVEF during stress. Results: Coronary flow velocity reserve (CFVR) was measured in 919 women of whom 26% had CMD (defined as CFVR < 2). Coronary microvascular dysfunction (CMD) was associated with higher age and a higher resting heart rate. Women with CMD had a reduced GLS reserve ( P = .005), while we found no association between CFVR and LVEF at rest, GLS at rest, or the LVEF reserve, respectively. Global longitudinal strain (GLS) reserve remained associated with CFVR ( P = .002) in a multivariable regression analysis adjusted for age, hemodynamic variables, and GLS at rest. In age‐adjusted analysis, women with low CFVR had no signs of left ventricular diastolic dysfunction measured by echocardiography at rest. Conclusion: The GLS reserve was significantly lower in women with CMD. The mechanisms underlying the association between CMD and GLS reserve warrant further study.